Long‐Lasting Auditory and Vestibular Recovery Following Gene Replacement Therapy in a Novel Usher Syndrome Type 1c Mouse Model - Weinan Du; Jun Huang; Aizhen Zhang; Fangfang Zhao; Tianwen Chen; Quinn M. McDermott; Tony Zheng; Haibo Wang; Rongli Zhang; Xiaolin Zhang; Jerome Allison; Hong Zhu; et al. (Advanced Science)
Abstract Usher syndrome type 1C (USH1C) is a genetic disorder caused by mutations in the USH1C gene, which encodes harmonin, a key component of the mechanoelectrical transduction complex in auditory and vestibular hair cells. USH1C leads to deafness and vestibular dysfunction in humans. An Ush1c knockout (KO) mouse model displaying these characteristic deficits is generated in our laboratory. To examine gene replacement therapy (GT) in this model, a synthetic adeno‐associated viral vector, Anc80L65, driving harmonin expression is administered, to the inner ears of Ush1c KO mice at postnatal day 2 (P2). Remarkably, this single treatment significantly improved auditory brainstem response (ABR) thresholds and balance motor function at 1 month post‐injection, with these effects persisting for up to 10 months. At 12 months post‐treatment, the vestibular function is assessed using the vestibular‐ocular reflexes (VOR) and single vestibular afferent recordings. The GT treatment significantly restored both the canal and otolith VORs and increased vestibular afferent spontaneous firing rates and responses to head rotation and translation. These findings provide the first evidence of long‐lasting restoration of both the auditory and vestibular functions by GT in a novel mouse model of Usher syndrome, highlighting the potential of GT for treating deficits associated with USH1C.